Non-invasive in vivo monitoring of PROTAC-mediated protein degradation using an environment-sensitive reporter - Li, Tao; Zong, Qingyu; Dong, He; Ullah, Ihsan; Pan, Zhenhai; Yuan, Youyong (Nature communications, 2025)
Proteolysis targeting chimeras (PROTACs) represent a groundbreaking therapeutic technology for selectively degrading proteins of interest (POIs). The structural variations in PROTACs unpredictably influence their protein degradation efficiency, which is predominantly assessed by quantifying POIs abundance through western blotting. This approach, however, falls short of enabling non-invasive monitoring of protein degradation within living cells let alone assessing directly the degradation effects in vivo. Herein, we develop an environment-sensitive reporter (ESR) for the quantification of protein degradation events triggered by PROTACs in vivo. By simultaneously integrating POIs targeting ligand and an environment-sensitive fluorophore, the ESR signals exhibit a strong fluorescence correlation with the levels of POIs. This non-invasive monitoring reporter offers a high-throughput and convenient way to screen POIs targeting degraders and predict PROTACs-mediated therapeutic outcomes in mouse models. These properties suggest the potential of ESR strategy as a general modular scheme for non-invasive quantification of protein degradation of cancer-related therapeutic targets. Proteolysis targeting chimeras (PROTACs) enable selective protein degradation but rely on invasive methods like western blotting to assess efficiency. Here, the authors develop an environment-sensitive reporter (ESR) for the non-invasive monitoring of PROTACs-mediated protein degradation in vivo.